Pharmacokinetic Drug Interaction Between Raloxifene and Cholecalciferol in Healthy Volunteers. Issue 5 (4th January 2022) - Lee, Hae Won; Kang, Woo Youl; Jung, Wookjae; Gwon, Mi‐Ri; Cho, Kyunghee; Lee, Backhwan; Seong, Sook Jin; Yoon, Young‐Ran
Abstract: Osteoporosis is a common skeletal disorder, often leading to fragility fracture. Combination therapy with raloxifene, a selective estrogen receptor modulator, and cholecalciferol (vitamin D3 ) has been proposed to improve the overall efficacy and increase compliance of raloxifene therapy for postmenopausal osteoporosis. To our knowledge, there has been no report of any study on the pharmacokinetic interaction between raloxifene and cholecalciferol. This study aimed to evaluate the possible pharmacokinetic interactions between raloxifene and cholecalciferol in healthy adult male Korean volunteers. Twenty subjects completed this open‐label, randomized, single‐dose, 3‐period, 6‐sequence, crossover phase 1 study with a 14‐day washout period. Serial blood samples were collected from 20 hours before dosing to 96 hours after dosing. The plasma concentrations of raloxifene and cholecalciferol were determined using a validated method for high‐performance liquid chromatography with tandem mass spectrometry. The geometric mean ratios (90%CIs) for area under the plasma concentration–time curve from time 0 to the last quantifiable time point and maximum plasma concentration of raloxifene with or without cholecalciferol were 1.02 (0.87‐1.20) and 0.87 (0.70‐1.08), respectively. For baseline‐corrected cholecalciferol, geometric mean ratios (90%CIs) of area under the plasma concentration–time curve from time 0 to the last quantifiable time point and maximum plasma concentration with or without raloxifene were 1.01 (0.93‐1.09) and 0.99 (0.92‐1.06), respectively. Concurrent treatment with raloxifene and cholecalciferol was generally well tolerated. These results suggest that raloxifene and cholecalciferol have no clinically relevant pharmacokinetic drug‐drug interactions when administered concurrently. All treatments were well tolerated, with no serious adverse events.